Information Technology Service Audit of Company X Using ITIL v4 Framework - Hartono, Maria Christina; Githa, Dwi Putra; Pasirulloh, Muhammad Alam (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 6 No 1 (2025): JITTER, Vol.6, No.1, April 2025, 2025)
Company X is responsible for providing clean water to the community, has a customer service information system for easy access to information, registration for new water connections, and complaints. This system still uses standard security, several times there are server down problems and IT services that need to be improved. The focus of the research uses the ITIL v4 framework subdomains Service Desk, Incident Management and Information Security Management. The results of measuring the maturity level of the customer service information system before collecting evidence of the Service Desk subdomain are at level 1, Incident Management and Information Security Management are at level 0, while the maturity level after collecting evidence of all subdomains is at level 5. The significantly different results indicate a lack of understanding of employees concerning the standardization of IT services that have been made so that recommendations are given in the form of socialization referring to the ITIL v4 guidelines.